SPEECH ACT OF COMMUNICATION STRATEGY BETWEEN THE DOCTOR AND THE PATIENT IN WALUYO JATI HOSPITAL, PROBOLINGGO - Hosnol Wafa; Azizetur Rohma (Program Studi Bahasa Inggris, Universitas Panca Marga, 2022)
Communication in medical is important thing because there are feedback between doctor and patient. Communication promotes both health and illness in society, and makes the system run at optimal or marginal effectiveness. This study applies pragmatics as based theory and speech act belongs to pragmatics. Illocutionary act are devided into five clarifications, namely assertives, directives, commisives, expressives, and declarations. Illocutionary act selected because most of the utterances in medical activity usually used its types. The research design in this study is descriptive qualitative method. Research area determination method use purposive sampling. Data collection method use observation. Data analysis method is data analysis qualitative by miles and huberman theory. Besides that, the data validity examination method using rechecking. The result of this study finds the types of illocutionary acts, they are asking directive act, explanation, ordering, requesting, advising, greeting answer, confirmation, fact assertive act, and prohibiting declaration act. Asking as mostly types of illocutionary act because the doctor presented the question is to get information about the complaint of the patient and improve the interaction between doctor and patient.